Agriculture, Livestock Production and Aquaculture Advances for Smallholder Farming Systems Volume 2 - Kumar, Arvind; Kumar, Pavan; Singh, S. S.; Trisasongko, Bambang Hendro; Rani, Meenu (Cham : Springer International Publishing : Imprint: Springer, 2022)
This two-volume set discusses recent approaches and technological innovations for sustainable agriculture in smallholder farming systems impacted by climate change. The systems covered include crop-based agricultural production, as well as aquaculture and livestock production as related systems using similar techniques to combat food security issues brought about by climate change and resource overuse. The chapters detail innovations involving crop diversification, soil resilience management, geoinformatics and land suitability monitoring for smart farming, information technology in livestock production, and nutrient resource management in fishery aquaculture. Researchers, practitioners and industries will be able to use this information to implement socially and economically sustainable practices to achieve food security in impoverished areas vulnerable to climate change, while also learning about the rapid evolution in information technology that is applicable for and available to small holder farmers. Volume 2 focuses on trends and technologies in food security within the context of sustainable practices, drone technology, microwave data, molecular farming, machine learning, agricultural economics, spatial modeling and agricultural policy. These chapters discuss advancements in fishery resource and aquaculture practices, and also the challenges facing these areas due to climate change. .
Chapter1. Drone Technology in Sustainable Agriculture: The future of farming is precision agriculture and mapping -- Chapter2. Revolutionizing Crops and Soil Resources' Resilience to Climate Change. A case for Best-fit Agronomic Practices in Low and High Input Systems -- Chapter3. Drought-resilient climate smart sorghum varieties for food and industrial use in marginal frontier areas of Kenya -- Chapter4. Optimizing nitrogen management for improved productivity, nitrogen use efficiency, food and nutrition security: African context perspectives -- Chapter5. Soil carbon pools under different farming practices -- Chapter6. Effect of conservation agriculture on energy consumption and carbon emission -- Chapter7. Plant Molecular Farming: A Marvelous Biotechnological Approach in Agricultural Production -- Chapter8. Examining the outcome of coupling machine learning with dual Polarimetric SAR for rice growth mapping -- Chapter9. Mapping prominent cash crops employing ALOS PALSAR-2 and selected machine learners -- Chapter10. Crop assessment and decision support information products using multi-sensor and multi-temporal moderate resolution data -- Chapter11. Agriculture, Livestock Production and Aquaculture: Advances for Smallholder Farming System -- Chapter12. Mobilizing Pig Resources for Capacity Development and Livelihood Security -- Chapter13. Agricultural Value Chains: A Cardinal Pillar for Future Development and Management of Farming -- Chapter14. Climate Smart Eco-management of Water and Soil Quality as a Tool for Fish Productivity Enhancement -- Chapter15. Advances in nutrient resource management for fisheries and aquaculture -- Chapter16. Conclusion.
Keywords: Environment; Agriculture; Food security; Sustainability; Environmental Sciences; Agriculture; Food Security; Sustainability